Effect of salinity on Echinochloa crus-galli germination as affected by herbicide resistance - Serra, Francesca; Fogliatto, Silvia; Vidotto, Francesco (Italian Journal of Agronomy, 2018)
Salinity is one of the major abiotic stresses that may affect yield and quality of crops. Salinization, in combination with the presence of aggressive weeds, such as barnyard grass (Echinochloa spp.), can be considered one of the factors responsible for reducing yield in rice fields. The aims of the study were to evaluate the salt effect on germination and first seedling growth of six different Italian common barnyard grass (E. crus-galli) populations (three sensitive and three resistant to ALS-inhibitor herbicides) and to verify the presence of differences in salt response between populations sensitive and resistant to the ALS-inhibitor herbicides. Germination tests were conducted under nine different NaCl concentrations (from 0 mM to 400 mM). Significant differences in germination capacity were found between sensitive and resistant populations from 0 mM to 250 mM NaCl; in particular, germination capacity of the sensitive populations was higher (up to 90%) than that of the resistant ones (about 70%). The increase in salinity over 250 mM reduced progressively the germination capacity: from 300 mM onwards, no significant differences were found between sensitive and resistant populations and the germination resulted inhibited for two of them (one sensitive and one resistant). Speed of germination and root and shoot length of seedlings were also inversely related to salt concentration. Time required for achieving 50% of final germination capacity was extended from about three days at 0 mM NaCl up to about 10-12 days at 400 mM NaCl. Root length and shoot length ranged from 9.88 cm and 6.16 cm, at 0 mM NaCl, to 0.36 cm and 0.41 cm, at 400 mM NaCl. According to the results, there is no a clear evidence that response to saline conditions was related to resistance towards ALS-inhibitor herbicides, as in some cases significant differences were found between populations showing a similar herbicide sensitivity. Responses of barnyard grass to salinity are may play a role in the importance of this weed in future scenarios of salt intrusion: for example, a lower speed of germination at increasing salt levels could suggest a delayed emergence of this weed during crop establishment and first growth. To evaluate the real consequences in terms of competitions towards the crop, future studies are needed for assessing the response to salinity of the main rice varieties cultivated in the environment in which the E. crus-galli populations tested in this study were collected.